Impact of citrate- and chitosan-capped gold nanoparticles on the liver of Swiss albino mice: Histological and cyto-genotoxic study - Zaki, Eiman I.; EL-Seedy, Ayman S.; Kelada, Inaam P.; Sharafeldin, Nadia A.; Abdel Mouaty, Hala M.; Ramadan, Heba S. (Cellular and Molecular Biology, 2019)
The present study aimed to disclose the histological alterations and cyto-genotoxic potential induced by citrate- and chitosan-capped AuNPs on liver of adult Swiss albino mice. Animals were randomly divided into 8 groups. The first two groups were intraperitoneally (i.p) injected with physiological saline once and left for 10 days and every other day for 21 days, respectively, and kept as negative control groups. While the third and fourth groups were injected i.p with a single dose of 2 mg/kg of citrate- and chitosan-capped AuNPs, respectively, and left for 10 days. The fifth and sixth groups were injected i.p every other day for 21 days with 200 µg/kg of citrate- and chitosan-capped AuNPs, respectively. Animals of the seventh and eighth groups were injected i.p with 50 mg/kg cyclophosphamide once and left for 10 days and with 20 mg/kg cyclophosphamide every other day for 21 days, respectively. The livers of mice were dissected and processed for microscopic examination and for analyzing the expression of inflammation-related genes using RT-PCR. In addition, bone marrow samples were taken to investigate the mitotic index and the chromosomal aberrations. The present study showed various degrees of structural changes in the liver of animals received AuNPs. Such changes were more prominent in animals treated with a single dose of AuNPs, particularly with citrate-capped AuNPs as compared to chitosan-capped AuNPs. Furthermore, genotoxic analysis did not reveal any genotoxicity for AuNPs with both coats. Therefore, chitosan-capped AuNPs were less hepatotoxic than citrate-capped ones. However, it has not been proven that AuNPs are genotoxic by both coats.